The Role of Women in the Development of Social Media Organizations Researchers - احمد, م.م. چنور احمد محمد; عبدالله‌, آ.م.د. كاروان عبدالله‌ محمد (Sulaimani Journal for Humanities, 2025)
Women, as strong social figures with various skills in different fields, contribute to either the progress or delay of the work of any institution. This is related to women's efficiency in different professions and across various organizations. Human capability in public relations depends on the skills of those involved in communication, which aligns with the progress and development of any institution. This study examines the role of women in the development of public relations within media institutions in the Kurdistan Region. For this purpose, the insights of senior and central managers of these media institutions were considered as the research community. The study was conducted using descriptive-analytical and survey methods to assess the level of women's proficiency in communication The role of these institutions in the development of media organizations. The aim of this study is to effectively represent women in public relations and their role in the growth and advancement of media institutions through these skills. The main question of the study is: 'What skills do women have in the communication process?' and how do women contribute to the development of public relations in media organizations. The most important findings of the study are: 1. The number of women involved in media relations management is lower than that of men. 2. Women are more proficient and effective communicators than men. 3. Women play a role in the development of media institutions due to their skills and dedication to scientific principles in communication.
Keywords: Communication Skills; Women; Media Organizations